Pengaruh Brand Image Produk Emina sebagai â€œMakeupTeenagerâ€ terhadap Keputusan Pembelian pada Siswi SMKN 2 Denpasar - Aryawan, I Wayan; Putri, Triana M. (Jurnal Kajian Ilmu Komunikasi, 2022)
Brand Image is set offaiths in a name, symbol or design and the impression of person are obtained based on information about facts and the nuse the brand, so the impression that appears relatively in long-term that formed in consumerâ€™s mind. In there search entitled â€œPengaruh Brand Image Produk Emina sebagai â€œMakeupTeenagerâ€ Terhadap Keputusan Pembelian Pada Siswi SMKN 2 Denpasarâ€, aims to find out the significant effect between brand image and purchasing decisions on Eminaâ€™s makeup products for high school students of SMKN 2 Denpasar. This research uses quantitative approach, with a subjectof 87 respondents from high school students of SMKN 2 Denpasar. Data collected by questionnaire distribution technique through online media. To solved the problem used assumption test technique, linear regression test, and coefficient of determination test. Based on analysis results known there is significant effect between brand image of Eminaâ€™s product as teenagerâ€™s makeup and purchasing decision for high school students of SMKN 2 Denpasar. From the calculation of correlation coefficient (r) obtained at 0.851 and determination coefficient (r2) obtained at 0.725, it shows that brand image of Eminaâ€™s product has a strong correlation of purchasing decisions with a contribution of 72,5%. Variable regression coefficient for brand image of Eminaâ€™s product (X) obtained at 1.142 , so if brand image of Eminaâ€™s product increased as 1, then purchasing decisions (Y) will increase at 1.142. Coefficient is positive, it means positive relationship between brand image of Eminaâ€™s product and purchasing decisions. The more brand image of Eminaâ€™s product rises, the more purchasing decisions increase